The Role of Exosomal miRNAs in Glioma: Biological Function and Clinical Application - Aili, Yirizhati; Maimaitiming, Nuersimanguli; Mahemuti, Yusufu; Qin, Hu; Wang, Yongxin; Wang, Zengliang (Frontiers in Oncology, 2021)
Gliomas are complex and heterogeneous central nervous system tumors with poor prognosis. Despite the increasingly development of aggressive combination therapies, the prognosis of glioma is generally unsatisfactory. Exosomal miRNA has been successfully used in other diseases as a reliable biomarker and even therapeutic target. Recent studies show that exosomal miRNA plays an important role in glioma occurrence, development, invasion, metastasis and treatment resistance. However, the association of Exosomal miRNA between glioma has not been systemically characterized. This will provide a theoretical basis for us to further explore the relationship between exosomal miRNAs and glioma, and also has a positive clinical significance in the innovative diagnosis and treatment of glioma.